IMPROVING ARABIC LANGUAGE LEARNING MOTIVATION THROUGH THE SPIRIT OF MAN JADDA WAJADA: A PRE-EXPERIMENTAL STUDY - Machmud Yunus; Hisyam Zaini (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
The improvement of motivation in learning Arabic by applying the principle of man jadda wajada is a strategic and relevant step. This principle not only motivates students to study earnestly but also shapes a positive mindset oriented toward success. The aim of this study is to observe the differences in learning motivation before and after the application of the man jadda wajada motivational phrase. Research Method: The research used a pre-experimental design with a one-group pre-test and post-test framework, utilizing a questionnaire that had undergone validity and reliability testing. The study was conducted with 33 respondents, using total sampling, and was carried out from August to December 2024. Research Results: The difference in learning motivation scores, with a positive shift (post-intervention scores higher than pre-intervention scores), was recorded in 26 students from the moderate motivation category, showing a significant change to 25 students in the high motivation category. The computed rank differences showed that the positive shift in the high motivation category was more dominant, with the average positive rank score higher than the negative rank score. Wilcoxon test analysis showed a significant difference between learning motivation scores before and after the man jadda wa jadda motivational intervention, with a Wilcoxon test result of p = 0.000 (α = 0.05).